A Control Architecture for Massive Adaptive Video Streaming Delivery - Giuseppe Cofano; Luca De Cicco; Saverio Mascolo (Proceedings of the 2014 Workshop on Design, Quality and Deployment of Adaptive Video Streaming, 2014)
The optimization of massive video delivery, with the purpose of improving user engagement by delivering the maximum available quality of experience (QoE) to users, is a hot topic. In this paper we propose a Network Control Plane (NCP) for video streaming aimed at jointly maximizing users QoE and network utilization by reserving bandwidth on a per-flow basis. The NCP is placed on top of the controlled network and cooperates with distributed buffer-based adaptation techniques implemented at the client. It is specifically designed to take into account scalability and adaptivity issues. No communication with external entities involved in the delivery process, such as other networks or the streaming server, is required. We provide a reference implementation and a performance evaluation through simulations.
Keywords: dash; control plane; application-awareness; adaptive streaming